Prior Beta-Blocker Therapy for Hypertension and Sex-Based Differences in Heart Failure Among Patients With Incident Coronary Heart Disease - Bugiardini, Raffaele; Yoon, Jinsung; Kedev, Sasko; Stankovic, Goran; Vasiljevic, Zorana; Miličić, Davor; Manfrini, Olivia; van der Schaar, Mihaela; Gale, Chris P; Badimon, Lina; Cenko, Edina (My University, 2020)
The usefulness of β-blockers has been questioned for patients who have hypertension without a prior manifestation of coronary heart disease or heart failure. In addition, sex-based differences in the efficacy of β-blockers for prevention of heart failure during acute myocardial ischemia have never been evaluated. We explored whether the effect of β-blocker therapy varied according to the sex among patients with hypertension who have no prior history of cardiovascular disease. Data were drawn from the ISACS (International Survey of Acute Coronary Syndromes)-Archives. The study population consisted of 13 764 patients presenting with acute coronary syndromes. There were 2590 patients in whom hypertension was treated previously with β-blocker (954 women and 1636 men). Primary outcome measure was the incidence of heart failure according to Killip class classification. Subsidiary analyses were conducted to estimate the association between heart failure and all-cause mortality at 30 days. Outcome rates were assessed using the inverse probability of treatment weighting and logistic regression models. Estimates were compared by test of interaction on the log scale. Among patients taking β-blockers before admission, there was an absolute difference of 4.6% between women and men in the rate of heart failure (Killip ≥2) at hospital presentation (21.3% versus 16.7%; relative risk ratio, 1.35 [95% CI, 1.10-1.65]). On the opposite, the rate of heart failure was approximately similar among women and men who did not receive β-blockers (17.2% versus 16.1%; relative risk ratio, 1.09 [95% CI, 0.97-1.21]). The test of interaction identified a significant (P=0.034) association between sex and β-blocker therapy. Heart failure was predictive of mortality at 30-day either in women (odds ratio, 7.54 [95% CI, 5.78-9.83]) or men (odds ratio, 9.62 [95% CI, 7.67-12.07]). In conclusion, β-blockers use may be an acute precipitant of heart failure in new-onset coronary heart disease among women, but not men. Heart failure increases the risk of death. Registration URL: https://www.clinicaltrials.gov. Unique identifier: NCT04008173.